2022
DOI: 10.1002/advs.202200744
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Conversion Evolution on Solid‐State Na–SeS2 Battery via In Situ TEM

Abstract: All‐solid‐state (ASS) Na–S batteries are promising for a large‐scale energy‐storage system owing to numerous merits. However, the high conversion reaction barrier impedes their practical application. In this work, the basic mechanism on how Se catalyzes the conversion reaction in the Na–S batteries is unraveled. The sodiation/desodiation of Na–SeS2 nanobatteries are systematically evaluated via in situ transmission electron microscopy (in situ TEM) with a microheating device. The real‐time analyses reveal an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…The ionic and electronic conductivity of the LFP‐additive mixtures were measured on symmetric cells to evaluate the different conducting effects of the LPSCl and AG55 additives. Considering Li–In is a mixed conductor, to strictly block the electron conduction, two LPSCl solid electrolyte pellets were used as ion conduction and electron insulation layers in the symmetric cells to study the ionic conductivity, [ 41 ] as shown in Figure 5g,h . Li–In foils were used as electrodes to maintain a stable LPSCl/Li‐In interface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ionic and electronic conductivity of the LFP‐additive mixtures were measured on symmetric cells to evaluate the different conducting effects of the LPSCl and AG55 additives. Considering Li–In is a mixed conductor, to strictly block the electron conduction, two LPSCl solid electrolyte pellets were used as ion conduction and electron insulation layers in the symmetric cells to study the ionic conductivity, [ 41 ] as shown in Figure 5g,h . Li–In foils were used as electrodes to maintain a stable LPSCl/Li‐In interface.…”
Section: Resultsmentioning
confidence: 99%
“…The SEM and TEM samples were transferred in an Ar‐protected holder. [ 41b ] TEM was measured at a cryogenic temperature of −170 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The charge transfer resistance R ct values of the V 2 O 3 @C/rGO and V 2 O 3 @C electrodes are 23 Ω and 98 Ω, and their SEI film resistance R sf values are 4 Ω and 45 Ω, respectively. The smaller R ct and R sf values of the V 2 O 3 @C/rGO electrode are more beneficial to electron and lithium ion transfer during the cyclic process. This result proves that the fast electron and lithium ion transfer rate of the V 2 O 3 @C/rGO electrode is the reason for its large reversible capacity and superior rate capability. The smaller R ct (19 Ω) after 100 cycles than the value of the V 2 O 3 @C/rGO electrode after five cycles (Figure S10) indicates superior conductivity and faster Li + diffusion, which are in agreement with the increase in capacity.…”
Section: Resultsmentioning
confidence: 79%
“…23 Therein, the sulfide-based SE with high ionic conductivity (over 10 −4 S cm −1 ) and small grain boundary resistance at room temperature is an ideal option to realize high rate and high active material loading SSBs. 24–28 Particularly, the ionic conductivity of reported sulfides can surpass 10 −2 S cm −1 at room temperature, such as Li 10 GeP 2 S 12 , Li 6.6 Sb 0.4 Si 0.6 S 5 I, and Li 6.5 Sb 0.5 Ge 0.5 S 5 I, which are even higher than the typical liquid electrolytes. 29–31 The ultrahigh ionic conductivity can meet the ionic percolation demand and make full use of active materials even at lower temperatures.…”
Section: Introductionmentioning
confidence: 95%